Disasters and economic damage : macro, meso and micro approaches - Van der Veen, Anne (Disaster Prevention and Management: An International Journal., 2004)
Tsunamis, droughts, earthquakes, hurricanes and floods are a constant threat to society. Where in the past the population at risk had to react on the consequences of disasters, at present society wants to be more in control. Due to the high costs of restoration, of the stress and of the loss of family and friends a proactive policy in order to prevent disasters or at least to minimize the impact is required. Previously published in: Disaster Prevention and Management, Volume 13, Number 4, 2004.